Outcome of patients with stage I immature teratoma after surveillance or adjuvant chemotherapy - Marino, Giuseppe; Grassi, Tommaso; De Ponti, Elena; Negri, Serena; Testa, Filippo; Giuliani, Daniela; Delle Marchette, Martina; Dell’Oro, Cristina; Fumagalli, Diletta; Donatiello, Gianluca; Besana, Giulia; Marchetta, Liliana; et al. (Frontiers in Oncology, 2024)
Immature teratomas are rare malignant ovarian germ cell tumours, typically diagnosed in young women, where fertility-sparing surgery is the treatment of choice. The role of adjuvant chemotherapy in stage I disease remains controversial. We evaluated the impact of surveillance versus chemotherapy on the recurrence rate in stage I immature teratomas.We collected a single centre retrospective series of patients with stage I immature teratomas treated with fertility-sparing surgery at San Gerardo Hospital, Monza, Italy, between 1980 and2019. Potential risk factors for recurrence were investigated by multivariate logistic regression.Of the 74 patients included, 12% (9/74) received chemotherapy, while 88% (65/74) underwent surveillance. Median follow-up was 188 months. No difference in recurrence was found in stage IA/IB and IC immature teratomas [10% (6/60) vs. 28.6% (4/14) (P=0.087)], grade 1, grade 2, and grade 3 [7.1% (2/28) vs. 14.3% (4/28) vs. 22.2% (4/18) (p=0.39)], and surveillance versus chemotherapy groups [13.9% (9/65) vs. 11.1% (1/9)) (p = 1.00)]. In univariate analysis, the postoperative approach had no impact on recurrence. The 5-year disease-free survival was 87% and 90% in the surveillance and chemotherapy groups, respectively; the overall survival was 100% in both cohorts.Our results support the feasibility of surveillance in stage I immature teratomas. Adjuvant chemotherapy may be reserved for relapses. However, the potential benefit of chemotherapy should be discussed, especially for high-risk tumours. Prospective series are warranted to confirm our findings.To date, no consensus has been reached regarding the role of adjuvant chemotherapy in stage I immature teratomas of the ovary. Some studies suggest that only surveillance is an acceptable choice. However, guidelines are not conclusive on this topic.No difference in terms of recurrence was observed between the surveillance and the adjuvant chemotherapy group. All patients who relapsed were successfully cured with no disease-related deaths.Adjuvant chemotherapy should be appropriately discussed with patients. However, it may be reserved for relapse according to our data.